Optimalisasi Literasi Digital dan Kreativitas Siswa Sekolah Dasar Melalui Pendekatan Learning by Doing Menggunakan Typingcore dan Microsoft Paint - Gumelar, R. Tommy; Purnamasari, Epa Apnan; Anjani, Dewi; Latifah, Latifah; Lestari, Yesi; Zakaria, Achmad; Chessario Ramdoni, Muhammad Ravael; Febriansyah, Rully; Abi Dahlan, Muhamad Atthalah; Hadiwijoyo, Mohammad Rafi (JPM: Jurnal Pengabdian Masyarakat, 2026)
The digital literacy gap in rural areas remains a major challenge in ensuring equitable education quality in Indonesia, particularly at the elementary school level which often lacks technological facilities. This service aims to optimize basic computer competence and stimulate student creativity through intensive mentoring. The service partners in this activity are elementary education institutions and the surrounding community identified as having limited access to information technology devices. The implementation method uses a Participatory Action Research (PAR) approach with a learning by doing technique focused on three main aspects: hardware introduction, ten-finger typing training using the interactive site Typingcore, and creative visualization using Microsoft Paint. The activity was carried out for six weeks involving active student participation and full support from village officials. The results showed a significant increase in students' understanding of computer device functions and increased fine motor skills in using the mouse and keyboard. Success indicators are seen from the ability of 100% of students to operate booting and shutdown procedures independently, an increase in average typing speed, and the creation of simple, original digital works as activity outputs. The implication of this activity is the formation of students' adaptive mindsets towards technology. In conclusion, the direct practice method proved effective in building children's self-confidence, reducing technology anxiety (technophobia), and becoming a feasible mentoring model to be replicated for areas with similar characteristics.